Security Architecture for Health Grid Using Ambient Intelligence - Naqvi, S.; Riguidel, M.; Demeure, I. (Methods of Information in Medicine, 2005)
Objectives: To propose a novel approach of incorporating ambient intelligence in the health grid security architecture.Methods: Security concerns are severely impeding the grid community effort in spreading its wings in health applications. In this paper, we have proposed a high level approach to incorporate ambient intelligence for health grid security architecture and have argued that this will significantly improve the current state of the grid security paradigm with an enhanced user-friendly environment. We believe that the time is right to shift the onus of traditional security mechanisms onto the new technologies. The incorporation of ambient intelligence in the security architecture of a grid will not only render a security paradigm robust but also provide an attractive vision for the future of computing by bringing the two worlds together.Results: In this article we propose an evolutionary approach of utilizing smart devices for grid security architecture. We argue that such an infrastructure will impart unique features to the existing grid security paradigms by offering fortified and relentless monitoring. This new security architecture will be comprehensive in nature but will not be cumbersome for the users due to its typical characteristics of not prying into their lives and adapting to their needs.Conclusions: We have identified a new paradigm of the security architecture for a health grid that will not only render a security mechanism robust but will also provide the high levels of user-friendliness. As our approach is a first contribution to this problem, a number of other issues for future research remain open. However, the prospects are fascinating.
Keywords: Grid computing; ambient intelligence; bioinformatics applications; security architecture